2021
DOI: 10.1590/1678-4162-12095
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield and composition in dairy cows with post-partum disorders

Abstract: This study aimed to determine the impact of different post-partum disorders on milk yield and composition. One hundred and fifteen Holstein cows from a commercial dairy farm located in the state of Rio Grande do Sul in southern Brazil were monitored up to 62 days post-partum. During this period, body condition score evaluation and animal clinical examination were conducted. Percentages of fat, protein, and lactose, as well as somatic cells score, were determined in milk samples. The AST activity and concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Milk fat can be a very interesting indicator for assessing metabolic stress in the form of lipolysis and ketogenesis, because it correlates with NEFA and BHB in the blood, so that the slope of the regression curve is similar in all periods of lactation, which gives additional value to this parameter. In earlier research, it was found that in cows with metabolic disease in early lactation there is a change in the value of milk fat and the milk fat to protein ratio [27]. Milk fat is an indicator to which special attention must be paid in the future, especially because this parameter is measured routinely and daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk fat can be a very interesting indicator for assessing metabolic stress in the form of lipolysis and ketogenesis, because it correlates with NEFA and BHB in the blood, so that the slope of the regression curve is similar in all periods of lactation, which gives additional value to this parameter. In earlier research, it was found that in cows with metabolic disease in early lactation there is a change in the value of milk fat and the milk fat to protein ratio [27]. Milk fat is an indicator to which special attention must be paid in the future, especially because this parameter is measured routinely and daily.…”
Section: Discussionmentioning
confidence: 99%
“…Milk parameters originate from blood and food components, and elucidating relationships among these parameters individually in food, blood and milk helps to understand the health and production status of animals [21][22][23][24][25]. Milk may be a preferred matrix whenever possible because it is non-invasive and easy to collect, and it is often used to identify ketosis and other production disease [26,27]. Variations in milk fat and milk BHB levels indicate lipomobilization and ketogenesis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The main feed in the summer is young green forage rich in protein, which increases milk yield (Auldist et al, 2013). In cows fed a TMR diet, these differences may be due to factors such as the stage of lactation or the animals' overall health condition (Jóźwik et al, 2012;Bondan et al, 2021). Differences in milk composition between seasons were described by many authors analysing milk from both organic farms (Kuczyńska et al, 2011) and conventional farms, mainly those using traditional feeding (Barłowska and Litwińczuk, 2006;Barłowska et al, 2013;Brodziak et al, 2020;Florio et al, 2022).…”
Section: Milk Yield and Compositionmentioning
confidence: 99%
“…Milk is a preferred matrix for monitoring the health status of dairy cows since it is non-invasive and easy to collect, and it is frequently used to identify ketosis and other production problems [1,2]. Milk fat and β-hydroxybutyrate (BHBA) levels vary, indicating lipomobilization and ketogenesis [3].…”
Section: Introductionmentioning
confidence: 99%